2016
DOI: 10.5455/medarh.2016.70.408-412
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Treatment of Anemia in Premature Infants

Abstract: Introduction:Anemia in preterm infants is the pathophysiological process with greater and more rapid decline in hemoglobin compared to the physiological anemia in infants. There is a need for transfusions and administration of human recombinant erythropoietin.Aim:To determine the frequency of anemia in premature infants at the Pediatric Clinic, University Clinical Center Sarajevo, as well as parameter values in the blood count of premature infants and to explore a relationship between blood transfusions with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 12 publications
3
8
0
Order By: Relevance
“…Admission duration was longer in the transfused group, a similar result with Jeon et al in 2013 in Korea [9].Complications during were more frequent in the transfused group, a result parallel to that of Banerje et al in 2015 in England [19].The overall mortality rate was 21.13% with a higher rate in the transfused group (12.68% vs. 8.45%) but not significant. This result is similar to those obtained by Hasenbegovic et al in 2010 in Bosnia [20] and Dick-Amon et al in 2014 in Côte d'Ivoire [14], which found 21% and 26% of the mortality rate respectively.…”
Section: Insupporting
confidence: 92%
“…Admission duration was longer in the transfused group, a similar result with Jeon et al in 2013 in Korea [9].Complications during were more frequent in the transfused group, a result parallel to that of Banerje et al in 2015 in England [19].The overall mortality rate was 21.13% with a higher rate in the transfused group (12.68% vs. 8.45%) but not significant. This result is similar to those obtained by Hasenbegovic et al in 2010 in Bosnia [20] and Dick-Amon et al in 2014 in Côte d'Ivoire [14], which found 21% and 26% of the mortality rate respectively.…”
Section: Insupporting
confidence: 92%
“…The reduced iron storage of preterm neonates at the time of birth, inability to breastfeed the infant within the first days or weeks of life, frequent blood sampling, and decreased level of erythropoietin (leading to anemia) are associated with frequent PCT during the hospitalization of premature infants (12). Although PCT is a lifesaving treatment, it can cause some complications for the newborn.…”
Section: Discussionmentioning
confidence: 99%
“…Preterm infants typically undergo numerous laboratory testing that require phlebotomy which may contribute to blood loss. (41) RBC transfusion is given to preterm infants if deemed necessary with the goal of increasing oxygen transport to the organs. (42) This study found non-significant relation between RBC transfusion and ROP with p=0.881.…”
Section: Discussionmentioning
confidence: 99%